PEMIKIRAN HOWARD FEDERSPIEL TERHADAP TAFSIR QUR’AN AL-KARIM KARYA MAHMUD YUNUS - yovik ir yana; dadan rusmana; Yayan Rahtikawati (Manarul Qur'an: Jurnal Ilmiah Studi Islam, 2022)
Efforts to combine the substance of the Qur'an with composing books are also interesting to observe. Apparently, so far there are many books that have been compiled as works to mingle the Qur'an with Muslims, be it as a book of understanding, investigation. Mahmud Yunus' work in Tafsir Qur'an al-Karim is a new example or model for writing Indonesian Tafsir. And the work was studied by one of the Western figures, Howard M. Federspiel with the title Popular Indonesian Literature Of The Qur'an. The method used is descriptive-analytical method, which is trying to describe how Howard Federspiel's thoughts on Tafsir Qur'an al-Karim. The purpose of this research study is to describe or explain Howard M. Federspiel's argument in Mahmud Yunus' Study entitled Tafsir Qur'an al-Karim. The theory that will be used as an analytical tool in this paper begins with the application of the structural interpretation theory initiated by Daniel Patte. This theory underlines that there is a mutually influencing relationship between the results of one's interpretation of a text and the cultural background of the mufassir. According to Howard Periodization of the history of the interpretation of the Qur'an in Indonesia, there are three periods, one of which is in the second generation, an Indonesian figure, Mahmud Yunus, was found. He is a reformer who is quite representative in his interpretation of the Arabic text and Latin writings as well as adding clear footnotes and sources. Keywords: Mahmud Yunus, Howard Federsfiel, Qur'anic interpretation.